Study Habits and Their Relationship with Academic Performance among Students of Abadan School of Nursing - Malek FereidouniMoghadam; Bahman Cheraghian (Kerman University of Medical Sciences, 2009)
Background & Objective : Improvement in learners academic performance is one of the main goals of educational centers Academic performance is affected by a lot of factors study habit is one of them Considering the importance of ones study habits in academic performance this study was conducted to identify the students study habits and their relationship with academic performance in Abadan School of Nursing   Methods : This cross sectional study was conducted on 150 students of Abadan School of Nursing in 2007 Data was collected using Palsane & Sharma Study Habit Inventory questionnaire which was completed in a selfdirected way at the time of holding final exams   Results : According to the results of this study the mean score ( ± SD) of the students study habits was 4826 ( ± 116) out of 90 1133 percent of the students had unsatisfactory study habits while 807% and 8% had relatively satisfactory and satisfactory study habits respectively There was a significant week and positive relationship between the students study habits and their academic performance (P=0001 r= 027) There wasnt any significant relationship between study habits and semester age and marital status   Conclusion : Generally speaking the students study habits are considered to be moderate that is to say that their study method is not of good quality Considering the importance of study habits in academic performance and achievement planning to improve students study habits and methods and interventions in this regard can be effective